Literacy Assistance Strategy for Group Guidance and Counseling to Increase Students' Interest in Reading at SDI Waewaru, Ngada District, 2024 - Wonga, Maria Tevian; Meka, Marsianus; Dhiu, Konstantinus Dua; Ngura, Elisabeth Tantiana (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
This research aims to determine the literacy assistance strategy for group guidance and counseling to increase students' interest in reading at SDI Waewaru, the research location was conducted at SDI Waewaru, Ngada district, Aimere subdistrict, the population consists of 1 class which is class III. There is still a low interest in reading among students at SDI Waewaru class III, especially for 6 students who have a very low interest in reading. Reading is one of the important things in all kinds of learning processes. It is through reading various knowledge that can lead to success that we can obtain. The method used in this research is a descriptive qualitative research method taken from the results of classroom learning observations, interviews, and documentation of student activities in the classroom learning process and literacy habits at school. The research results show that interest in reading is still relatively low due to several factors such as lack of reading habits, lack of parental support to motivate students to increase children's interest in reading, and lack of teacher creativity in developing students' reading skills.